Spatial Analysis for Fire Risk Reduction in Kampung Ampel Cultural Heritage Area, Surabaya - Farida Hudanti; Takeyuki Okubo; Petrus Natalivan Indradjati (Geoplanning: Journal of Geomatics and Planning, 2020)
The objective of the research is to improve fire risk reduction in Kampung Ampel Surabaya through: [1] identifying the current firefighting system in Surabaya; [2] identifying the characteristics and conditions of Kampung Ampel; [3] identifying structure of the problem; [4] proposing strategies for fire risk reduction in Kampung Ampel. The analysis will focus on determining risks and resources of Kampung Ampel to fire hazard using Geographic Information System (GIS) analysis. Risk and resources are combined to find out the areas that have the highest risk of fire hazard. The results of the analyses consist of challenges and possible solutions. The challenges can be concluded as follow: [1] resources for firefighting cannot cover the entire area of Kampung Ampel; and [2] resources for evacuation cannot accommodate all the population and visitors. The proposed solutions for those challenges are: [1] reactivation of inactive fire wells; [2] utilization on source of water in Ampel Mosque; [3] proposing wider road to connect roads which are wider than 3.5 meters but are blocked by narrower roads; [4] the purchase of adapters to connect different types of fire hoses; [5] adding the number of fire hoses brought to the site; [6] remodeling the vulnerable buildings using inflammable materials with keeping the value of cultural landscape; [7] keeping portable fire pump in Ampel Mosque to facilitate the fire handling by residents; and [8] preparing evacuation route to the closest open space areas. The application of those solutions can reduce the high-risk area from 26.6% to 0.2%.